2021
DOI: 10.1371/journal.pone.0255331
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice on first aid management of choking and associated factors among kindergarten teachers in Addis Ababa governmental schools, Addis Ababa, Ethiopia. A cross-sectional institution-based study

Abstract: Background Choking refers to a blockage of upper airways by food or other objects resulting in interruption of breathing. It is a medical emergency that needs immediate action by anyone near by the victim to save life. Chocking is a major cause of illness and death in the pediatric population under the age of 5 years. Children at this age spent more time in their school and are at high risk during their feeding and playing. Immediate provision of first aid in response to choking by a preschool teacher will hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
14
0
3
Order By: Relevance
“… 30 Furthermore, in Addis Ababa, 37.6% of kindergarten teachers exhibited proficiency in choking initial aid procedures. 31 Collectively, these findings show variable levels of knowledge in different communities about choking—a potentially fatal incident that can be resolved with simple first-aid procedures.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 30 Furthermore, in Addis Ababa, 37.6% of kindergarten teachers exhibited proficiency in choking initial aid procedures. 31 Collectively, these findings show variable levels of knowledge in different communities about choking—a potentially fatal incident that can be resolved with simple first-aid procedures.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies conducted in various countries, including Saudi Arabia, Turkey, Ethiopia, and Japan, have explored awareness and knowledge related to choking. 23 33 Our literature review revealed a widespread lack of knowledge about choking in many countries. Notably, a study conducted in Saudi Arabia revealed that 61.3% of parents in the Al Qassim region and 65.4% of parents in Makkah possessed inadequate knowledge regarding choking, with 55.3% of parents in Al Qassim and 78.6% of parents in Makkah exhibiting unsatisfactory practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Turkish study showed that 46% of respondents had received information about first aid or attended a first-aid course [ 16 ]. According to an Ethiopian study, 46% of respondents had received a first-aid course [ 17 ], while two studies in Saudi Arabia showed that 26% and 30% of respondents had attended a first-aid course, respectively [ 18 , 22 , 23 , 24 , 25 , 26 , 27 ]. Taken together, the findings of the present study clearly indicate that a considerably larger share of Belgian teachers have some experience with first-aid courses, compared with select countries in Africa and Asia.…”
Section: Discussionmentioning
confidence: 99%
“…When focusing on first-aid knowledge among primary school teachers in Flanders, no studies have been conducted on this topic to the best of our knowledge. Studies investigating teachers’ first-aid knowledge in other countries have shown that it is often insufficient [ 2 , 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], and first-aid training is paramount to improve this knowledge [ 26 , 27 ]. The aim of this study is to map the objective and subjective first-aid knowledge among teachers in primary education (kindergarten and primary education) in Flanders, Belgium, and to study which individual characteristics are linked with the subjective and objective knowledge of first aid.…”
Section: Introductionmentioning
confidence: 99%